Liberia : Third Review under the Extended Credit Facility Arrangement and Request for Waivers of Nonobservance of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2021)
Ensuring macroeconomic stability, providing a foundation for sustainable and inclusive growth, and addressing weak governance are the tenets of the ECF-supported program. The COVID-19 pandemic was a painful setback, but economic activity should recover by end-2021 and prospects for growth in 2022 are favorable. Prudent monetary and fiscal policies allowed inflation to decline into the single digits. The authorities are addressing disruptive currency shortages through a comprehensive currency changeover operation. While the SDR allocation provides timely room for supportive policies without compromising macroeconomic stability, the authorities remain committed to their reform program and generally continue to implement the necessary measures.